Diversity of Free-Living and Particle-Attached Prokaryotes in a River-Influenced Coastal Area of the Northern Adriatic Sea - Trano, Anna Chiara; Piredda, Roberta; Balestra, Cecilia; Bastianini, Mauro; Gasol, Josep M.; Casotti, Raffaella (Frontiers in Marine Science, 2022)
The Northern Adriatic Sea represents a key area of the Mediterranean Sea, being strongly affected by freshwater inputs, mainly from the Po River, which brings high amounts of nutrients as well as organic and inorganic particles. Free-living and particle-attached prokaryotes were characterized by 16S rRNA gene amplicon sequencing of size-fractionated samples collected during a diatom bloom. The diversity of free-living and particle-attached prokaryotic assemblages was investigated with the aim to understand how the microbial communities are structured in the two fractions and whether specific microbial groups belong to one or the other lifestyle. The results highlight a diverse prokaryotic community dominated by Proteobacteria, Bacteroidetes and Firmicutes. Taxa within Firmicutes and Alphaproteobacteria have been identified as main particle-attached indicators by LEfSe analysis, while members of Bacteroidetes and Gammaproteobacteria as free-living indicators, although they are usually found as particle-attached. Collectively, the results suggest that free-living or particle-attached lifestyle can be influenced by the trophic state and general environmental conditions even though specializations occur.